Reproductive Ecology of Dragonfishes (Stomiiformes: Stomiidae) in the Gulf of Mexico - Marks, Alex D.; Kerstetter, David W.; Wyanski, David M.; Sutton, Tracey T. (Frontiers in Marine Science, 2020)
The most abundant fishes on Earth live in the meso- and bathypelagic (deep-pelagic, collectively) zones of the open ocean, where they play a key role in deep-sea food webs by mediating energy flow from surface waters to great depth. Of these fishes, the most speciose taxon is the family Stomiidae (dragonfishes). Despite being the numerically dominant predators of the global mesopelagic zone, stomiid reproductive ecology is poorly known. Research surveys rarely catch larger adults, impeding reproductive ecology studies. Between 2010-2011, the Offshore Nekton Sampling and Analysis Program sampled the Gulf of Mexico using a research-sized, opening/closing trawl (10-m2 MOCNESS) and a commercial-sized, high-speed rope trawl (HSRT). Size-distribution analysis by gear type revealed: the HSRT caught more specimens per species, and the HSRT caught significantly larger specimens, whereas the MOCNESS sampled more juveniles. Gonads were dissected from 714 individuals representing 47 species, and the 12 dominant species were analyzed in further detail. Gonadal histology assessment indicated that stomiids are gonochoristic and exhibit asynchronous oocyte development and batch spawning. A total of 11 of the 12 species had sex ratios that did not significantly differ from a 1:1 (male:female) ratio (P < 0.05). Histological analysis indicated that females mature at larger sizes than males. Given the lack of age and growth data for this family, these data are critical for estimating stomiid production rates, a key element for quantifying the role of stomiids in the transfer of organic matter within the deep-pelagic zone, the planet’s largest cumulative ecosystem.